2014
DOI: 10.1097/ruq.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Correlation Between Semen Analysis Parameters and Intraparenchymal Testicular Spectral Doppler Indices in Patients With Clinical Varicocele

Abstract: Spectral Doppler analysis can provide valuable information as a noninvasive method to assess the hemodynamic changes and testicular microcirculation status in cases of clinical varicocele. However, RI, PI, and EDV values of capsular and intraparenchymal branches of testicular arteries may not be used as indicators of semen parameter deterioration. Hopefully, PSV measurement may give more conclusive data to predict sperm count. In addition, the cutoff value for this index has to be determined for future studies. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 35 publications
(19 reference statements)
2
32
0
2
Order By: Relevance
“…Similar results were reported in other studies. [37][38][39][40] Present study showed that although RI values were not different in groups with normal and pathological semen parameters, SRs were found to have a positive relationship with RIs in Group 2.…”
Section: Discussionmentioning
confidence: 85%
“…Similar results were reported in other studies. [37][38][39][40] Present study showed that although RI values were not different in groups with normal and pathological semen parameters, SRs were found to have a positive relationship with RIs in Group 2.…”
Section: Discussionmentioning
confidence: 85%
“…Varicocele can be easily shown with standard ultrasonographic examinations and can be confirmed by color Doppler ultrasound (CDU), which provides a noninvasive assessment of testicular arterial and venous structures [1]. The problem with the varicocele is not in the diagnosis, which is quite easy, but with further management.…”
Section: Discussionmentioning
confidence: 99%
“…Because varicocele is a vascular DOI: 10.1159/000500027 event, there have been many studies focused on vascular structures to provide information about pathophysiology and effects of varicocele on testis parenchyma [1]. As a noninvasive method color/spectral Doppler ultrasound analysis was tried to provide valuable information to assess the hemodynamic changes and testicular microcirculation status in cases of clinical varicocele.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography (US) is currently the most established and widely used modality for the study of varicoceles, with 97% sensitivity and 94% specificity in the diagnosis of clinical varicocele and 83%-95% sensitivity in the diagnosis of subclinical varicocele[5,12,13,33,36,37]. The classic US features of a varicocele is that of “multiple, anechoic, serpiginous, tubular structures” near the superior and lateral aspects of the testis.…”
Section: Diagnosismentioning
confidence: 99%
“…However, in subsequent studies, CDUS proved to be sensitive in assessing alterations in intratesticular circulation in testes with clinical varicocele[37,49,54-56]. A significant decrease in testicular arterial blood flow and an increase in RI and PSV in testes with clinical varicocele were reported[37,49,54-56].…”
Section: Us In the Evaluation Of Intratesticular Microcirculation In mentioning
confidence: 99%